WISDOM IN INVERTED COMMAS: GREEK COMEDY AND THE QUOTABLE MAXIM. (December 2022) - Wright, Matthew
Abstract : Greek comedy is full of quotable maxims. According to a literal reading, the comedians might be seen as custodians of traditional gnomic wisdom, along with their tragic counterparts. Nevertheless, it is argued here that maxims in comedy are different from maxims in other contexts. Comic maxims typically appear 'within inverted commas', not just in a literal sense (because of their inherent 'quotationality') but in a figurative sense (because of their pervasive irony and self-consciousness). Examples from Menander, Antiphanes, Diphilus and others are used to demonstrate that the comedians can be seen as playing around with the content and form of traditional wisdom. Sometimes they seem to be poking fun at the maxim as a medium of expression, or at tragic maxims, or at the habit of quotation itself.